Suppression of a Prolyl 4 Hydroxylase Results in Delayed Abscission of Overripe Tomato Fruits - Perrakis, Andreas; Bita, Craita E.; Arhondakis, Stilianos; Krokida, Afrodite; Mekkaoui, Khansa; Denic, Dusan; Blazakis, Konstantinos N.; Kaloudas, Dimitrios; Kalaitzis, Panagiotis (Frontiers in Plant Science, 2019)
The tomato pedicel abscission zone is considered a model system for flower and fruit abscission development, activation and progression. O-glycosylated proteins such as the Arabidopsis IDA (INFLORESCENCE DEFICIENT IN ABSCISSION) peptide and Arabinogalactan proteins (AGPs) which undergo proline hydroxylation were demonstrated to participate in abscission regulation. Considering that the frequency of occurrence of proline hydroxylation might determine the structure and as well the function of such proteins, the expression of a tomato prolyl 4 hydroxylase, SlP4H3, (Solanum lycopersicum Prolyl 4 Hydroxylase 3), was suppressed in order to investigate the physiological significance of this post-translational modification in tomato abscission. Silencing of SlP4H3 resulted in the delay of abscission progression in overripe tomato fruits 90 days after the breaker stage. The cause of this delay was attributed to the downregulation of the expression of cell wall hydrolases such as SlTAPGs (Tomato Abscission Polygalacturonases) and cellulases as well as expansins. In addition, minor changes were observed in the mRNA levels of two SlAGPs and one extensin. Moreover, structural changes were observed in the silenced SlP4H3AZs (Abscission Zones). The fracture plane of the AZ was curved and not along a line as in wild type and there was a lack of lignin deposition in the AZs of overripe fruits 30 days after breaker. These results suggest that proline hydroxylation might play a role in the regulation of tomato pedicel abscission.